ChemInform Abstract: Efficient Catalysis of the Aerobic Baeyer—Villiger Oxidation over a Bifunctional Catalyst Based on Cobalt Tetraphenylporphyrin Intercalated into Zn2Al Hydrotalcite. Issue 24 (June 2015) - Zhou, Weiyou; Tian, Peng; Sun, Fu'an; He, Mingyang; Chen, Zaixin
Abstract: The catalyst promotes both the oxidation of benzaldehyde to the corresponding percarboxylic acid and the conversion of cyclic ketones into lactones.